The wound healing property of ethanolic extract of Michelia champaca flowers in diabetic rats - Gowda, Amoolya; Shanbhag, Venkatesh; Bangalore, Eesha Rao; Shenoy, Smita; Prabhu, Krishnananda; Narayanareddy, Mukunda; Shanbhag, Tara (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The plant Michelia champaca (MC) is widely used in the treatment of inflammation, constipation, dysmenorrhea, ulcers, wounds, fever, and cough. The aim was to evaluate the wound healing property of ethanolic extract of MCflowers in streptozotocin-induced diabetes in rats. Methods: Wound healing activity was assessed by incision and excision wound models. Five groups of n=6 rats and n=14 rats were used for incision and excision wound models, respectively. Group I rats, non-diabetic control and Group II rats diabetic control, received 1 ml of 0.5% caboxymethylcellolose, which was used to prepare a suspension of ethanolic extracts of MC. Group III, IV and V rats were given MC extract the suspension of 100 mg/kg, 200 mg/kg and 300 mg/kg respectively. Parameters observed were breaking strength of incision wound and wound contraction, epithelialization, hydroxyproline content of excision wound respectively. Results were analyzed using one-way analysis of variance, followed by Tukey’s post-hoc test. Results: Breaking strength, rate of wound contraction and hydroxyproline content were significantly increased, and the period of epithelialization was significantly reduced in Group IV and V rats respectively. Conclusion: Oral administration of ethanolic extract of MC promotes wound healing in diabetic rats. Hence, further study in humans is suggested.